Pengaruh Electronic Word of Mouth dan Brand Image @avoskinbeauty terhadap Brand Trust - Bambang Sujarwadi; Dhety Chusumastuti; Arum Mawarti; Virginia Maharani (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The phenomenon of growth in Indonesia’s beauty industry has intensified competition among both global and local skincare brands, including Avoskin. This situation impacts consumer trust Instagram. Avoskin must compete to build brand trust amid the higher exposure and engagement dominance of global brands on social media. Challenges such as the presence of negative reviews and unfavorable consumer perceptions that lead to dissatisfaction represent significant threats to Avoskin’s ability to sustain brand trust. This study aims to determine the influence of electronic word of mouth and brand image of @avoskinbeauty toward brand trust. The research adopts a quantitative approach using the simple random sampling method, involving 400 active Instagram users as respondents. Data were collected through Google Forms and analyzed using IBM SPSS Statistics 30.. The T - test results show that Avoskin’s electronic word of mouth on Instagram has a positive and significant effect on brand trust, with a tcount greater than the ttable value (8.335 > 1.965) and significance < 0.001 < 0.05. Similarly, Avoskin’s brand image also has a positive and significant impact on brand trust, with a tcount greater than the ttable value (22.462 > 1.965) and significance < 0.001 < 0.05. The F - test results indicate that electronic word of mouth and brand image simultaneously have a significant effect on brand trust, with an Fcount greater than the Ftable value (870.240 > 3.02) and significance < 0.001 < 0.05. In conclusion, electronic word of mouth and brand image play essential roles in enhancing brand trust. The implication of this study is that skincare companies should continuously strengthen their digital presence, consistently manage their brand image, and actively facilitate and respond to electronic word of mouth, especially on social media platforms.